Rancangan Penyempurnaan Sistem Seleksi Manager Finance & Accounting di PT Stamina Trimegah Perkasa - Lie, Stanley Rei Nevan; Saragih, Eva Hotnaidah (Journal of Emerging Business Management and Entrepreneurship Studies, 2022)
Strategic management has been praised for presenting firms with advantages. However, empirical evidence for its impact on firms under challenging conditions still needs empirical evidence. This study evaluates a unique situation in which firms facing the same external threat could end up differently. The relationships between strategic management and firms’ survival abilities were investigated by surveying 67 nickel-mining firms on Sulawesi Island, Indonesia. Each firm’s level in strategic management was measured by a questionnaire based on a two-dimensional model for strategic management maturity comprising process and leadership dimensions. Meanwhile, a firm’s survival ability was assessed in six facets, including detecting a threat, formulating an anticipation plan, implementing the plan, maintaining operations, maintaining performance, and continuing to exist in the future. Regression techniques were employed in the analysis. Proof of the positive effect that strategic management has on firms’ survival is delivered as the main result. It is further found that maturity in strategic management plays a more dominant role than strategic leadership. The effects of both dimensions in strategic management maturity on each survival ability facet are also explored.